Silver Hexacyanoferrate (III) on a Hybrid Graphene Oxide/PAMAM Dendrimer Surface and Application as an Electrocatalyst in the Detection of Isoniazid - Fernandes, Daniela Silvestrini [UNESP]; Bonfim, Kely Silveira [UNESP]; Carmo, Devaney Ribeiro do [UNESP] (Wiley-Blackwell, 2018)
The polyamidoamine dendrimer PAMAM was covalently bound to graphene oxide via amide formation between any peripheral amine group dendrimer and the carboxyl groups present in graphene oxide. This material (GOP) was characterized by different spectroscopic techniques, namely Raman Spectroscopy, X-Ray Photoelectron Spectroscopy (XPS), Fourier Transform Infrared Spectroscopy (FT-IR) and X-Ray Diffraction (XRD). The hybrid material was shown to adsorb silver, that in turn complexes with hexacyanoferrate (III) ions (GOPAgH). The complexed hybrid material was electrochemically investigated using cyclic voltammetry. Some electroanalytical parameters, such as different supporting electrolytes, the supporting electrolyte concentrations, hydrogen ion concentration effects and scan rate were evaluated in order to obtain optimum responses. The GOPAgH material was successfully tested in the electrocatalytic detection of Isoniazid using a graphite paste electrode with Limits of Detection and Quantification of 5.0x10(-6)molL(-1) and 1.7x10(-5)molL(-1), respectively.
Keywords: Hybrid Graphene Oxide; Polyamidoamine Dendrimer; Spectroscopy; Voltammetry; Isoniazid